LDL-cholesterol versus non-HDL-to-HDL-cholesterol ratio and risk for coronary heart disease in type 2 diabetes. (November 2014) - Eliasson, B; Gudbjörnsdottir, S; Zethelius, B; Eeg-Olofsson, K; Cederholm, J
Aims: We assessed the association between different blood lipid measures and risk of fatal/nonfatal coronary heart disease (CHD), which has been less analysed previously in type 2 diabetes. Design, methods: Observational study of 46, 786 patients with type 2 diabetes, aged 30–70 years, from the Swedish National Diabetes Register, followed for a mean of 5.8 years until 2009. Baseline and updated mean low-density lipoprotein (LDL)-, high-density lipoprotein (HDL)-, non-HDL-cholesterol, and non-HDL-to-HDL-cholesterol ratio were measured. Results: Hazard ratios (HR) for CHD with quartiles 2–4 of baseline lipid measures, with lowest quartile 1 as reference: 1.03–1.29–1.63 for LDL; 1.23–1.41–1.95 for non-HDL; 1.29–1.39–1.57 for HDL; and 1.31–1.67–2.01 for non-HDL:HDL, all p < 0.001 except for quartile 2 of LDL, when adjusted for clinical characteristics and nonlipid risk factors. A similar picture was seen with updated mean values. Splines with absolute 6-year CHD rates in a Cox model showed decreasing rates only down to around 3 mmol/l for LDL, with linearly decreasing rates to the lowest level of non-HDL:HDL. Non-HDL and HDL were independent additive risk factors for CHD risk. HRs per 1 SD continuous decrease in baseline or updated mean HDL were 1.14–1.17 when fully adjusted as above, and 1.08–1.13 when also adjusted for non-HDL ( p < 0.001). HRs were 1.13–1.16 adjusted for LDL, and 1.22–1.26 adjusted for total cholesterol and triglycerides ( p < 0.001). Splines showed progressively increasing 6-year CHD rates with lower HDL down to 0.5 mmol/l. Conclusions: This study suggests that lower levels of non-HDL:HDL are a better risk marker for CHD than LDL-cholesterol below 3 mmol/l.